2017
DOI: 10.1007/s11695-017-2740-4
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophic Scars: Are Vitamins and Inflammatory Biomarkers Related with the Pathophysiology of Wound Healing?

Abstract: There is a different systemic inflammatory profile response in the patients during the formation of hypertrophic scars. Vitamin D plasma levels are marked reduced in these patients. Considering the powerful anti-inflammatory effect of vitamin D, these findings could be related.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…4 Also, the availability of micronutrients and amino acids is critical for wound healing, and systemic supplementation of vitamins, iron, and thyroid hormones are known to improve wound healing. 15,16 However, there are challenges in their use for augmenting wound healing because of the existence of several biochemical and physiological barriers. The treating clinicians hence face challenges in the treatment of nonhealing wounds probably as a result of various coexisting factors and comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Also, the availability of micronutrients and amino acids is critical for wound healing, and systemic supplementation of vitamins, iron, and thyroid hormones are known to improve wound healing. 15,16 However, there are challenges in their use for augmenting wound healing because of the existence of several biochemical and physiological barriers. The treating clinicians hence face challenges in the treatment of nonhealing wounds probably as a result of various coexisting factors and comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from local wound care, other coexisting conditions and systemic factors also have to be addressed to achieve successful wound healing and standardized care for wound treatment, as emphasized by many physicians and authors. [15][16][17] As reported by Mani et al, 17 DFUs usually have associated neuropathy and infection, making healing complicated, whereas venous ulcers are associated with changes in the veins, increased capillary permeability, hemosiderin deposition in tissues, skin dryness, and thickening of skin. Thus, a holistic approach that includes standardized wound care, specific systemic therapies, and supportive measures such as offloading in DFU, compressions in venous ulcers, and newer technologies such as radio frequency (electromagnetic) stimulation 30,31 may be needed for successful wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Scars were evaluated at 6 months after surgery, and hypertrophic scars—defined as scars elevated above or beyond the original wound boundaries—were observed in 27% of patients. The patients who developed hypertrophic scars had significantly lower circulating 25(OH)D levels compared to patients who did not develop hypertrophic scars (15.46 vs. 23.52 ng/mL, respectively) 106 . In another study conducted in Turkey, Ince et al reported on 84 patients presenting to their outpatient clinic with existing linear hypertrophic scars resulting from prior surgeries on the trunk or extremities 107 .…”
Section: Keloids: More Than Just ‘Scars’mentioning
confidence: 99%
“…have been two studies that reported associations between vitamin D deficiency and hypertrophic scar formation in surgical patients. In the first, Correia-Sa et al examined hypertrophic scar formation in a cohort of 62 patients in Portugal undergoing bodycontouring surgery 106. Scars were evaluated at 6 months after surgery, and hypertrophic scars-defined as scars elevated above or beyond the original wound boundaries-were observed in 27% of patients.…”
mentioning
confidence: 99%
“…Among burn cases with systemic inflammation, the patients who undergo reconstructive surgery have been shown to develop scarring within 1 year [38]. Predisposing factors for scar development include A blood group, hyperimmunoglobulin E syndrome (high allergy risk), Afro-American, and Asian ethnicity [43].…”
Section: Hot Topics In Burn Injuriesmentioning
confidence: 99%